Enhancing Islamic Education Adaptability through Classical Management in the Digital Era - Bahri, Saiful; Irwansyah, Irwansyah; Subandi, Subandi; Makbuloh, Deden (Ahlussunnah: Journal of Islamic Education, 2025)
This study investigates the implementation of Lewin’s Change Management Model in managing institutional transformation at Pondok Pesantren Diniyah Putri Lampung, a faith-based Islamic educational institution navigating digital era challenges. Employing a qualitative case study approach, the research collected data through interviews, observations, document analysis, and teacher surveys to explore how the unfreezing, moving, and refreezing phases were adapted within the pesantren’s Islamic value system. The findings reveal that change was initiated through reflective awareness and spiritual framing, presenting digital transformation as a form of tajdid (renewal) rooted in religious duty. Strategic actions in the moving phase included teacher training, e-learning integration, and moral validation of digital content, while the refreezing stage saw institutionalization through updated policies, mentoring networks, and embedding Qur’anic values in daily digital practices. The study demonstrates that Lewin’s model can be effectively contextualized in Islamic settings through value-based leadership and culturally grounded strategies. It concludes that sustainable change in pesantren requires moral legitimacy, participatory engagement, and alignment between innovation and tradition. These findings contribute to broader theoretical discourse on managing educational change in faith-based environments and offer practical recommendations for Islamic educational leaders seeking modernization without compromising their spiritual identity.